ANTI-WEBSITE DEFACEMENT SYSTEM - Trần Đắc Tốt; Đặng Lê Nam; Phạm Nguyễn Huy Phương (Tạp chí Khoa học Đại học Đà Lạt)
Recently the impacts of hackers’ attacks which change the interface and content of Website are particularly serious. Therefore, there should be methods to allow real-time detection of these changes to reduce the consequences of these attacks. This article presents a new method to detect the changes of the interface and content of Website. Our proposed method is developed based on the HTML Boyer-Moore algorithm combined with the MD5 hash function and has been built into an application with a user-friendly interface. Moreover, we applied C4.5 algorithm to enhance the accuracy of the warning messages. Changes to the Website such as inserting new content, deleting or editing old content, changing the format, color, size, and type of content will be immediately recorded and notified to the Website administrator. The application will also highlight the locations of these changes and send a warning message and recommendations to the webmaster for processing. Experiment results show that the proposed method can accurately locate and produce spontaneous warnings to the Website administrator.